Challenges in preventing vertical HIV transmission in Petrolina, Pernambuco and Juazeiro, Bahia - Mucio do Nascimento Brandão; Edvaldo da Silva Souza; Rodrigo José Videres de Brito; Cavalcanti, Martha Maria de Souza Guimarães; Maria de Fátima Ramos Brandão; Magna Cavalcante e Cavalcante
Abstract Objectives: to measure vertical HIV transmission rate (TTV) and describe the adoption of prophylactic measurements (MP) in infected pregnant women and exposed children in the cities of Petrolina, PE and Juazeiro, BA. Methods: a cross-sectional study was carried out on 76 mothers and children from January 2006 to December 2010. Data were collected from reported forms and medical records from the referral services. The Ministry of Health recommendations was followed to characterize an infected child. It was appropriately considered to adopt the five MP distributed in three stages of care: pregnancy (antiretroviral therapy), intrapartum (intravenous azidotimidina and by delivery preference as a function of the maternal viral load) and post natal (azidotimidina taken orally by children and no breastfeeding). Results: 58 children investigated, five were HIV infected, revealing 8.6% of TTV. The MP was inadequate in 68.4% of the cases. Conclusions: high TTV of HIV and inadequate MP in most of the cases, the non-white patients and those who came from other cities received a lower proportion of adequate MP. Diagnostic failures and the three stages of care reflected on the TTV. Improve quick tests at pregnancy, integrate actions in cities, offer reproductive planning, maximize coverage of prenatal care and engage obstetric teams and Family Health are strategies to reduce TTV.